Peran Perguruan Tinggi Dalam Memberikan Perlindungan Terhadap Kekerasan Seksual Pada Perempuan Di Lingkungan Kampus - Parlindungan S, Gokma Toni; Suganda, Yohana; Putri, Selvi Kurnia; Januar, Ridwan Panasuri (Journal of Global Legal Review, 2023)
Universities have formed a task force for the Prevention and Handling of Violence against Women (PPKS) based on the results of a survey through the Character Strengthening Center (Puspeka) of the Ministry of Education and Culture, which was conducted on 106 PTNs and 36 PTSs. The results show that the majority of universities have adopted innovations in implementing PPKS, especially in terms of governance, socialization and reporting facilities. The survey revealed that 76 percent of PTNs and 61 percent of PTSs now provide sexual violence reporting services on campus. Apart from that, 65 percent of new students have taken the PPKS module set by the Ministry of Education and Culture until June 2023. Violence against women can happen to anyone and at any time. This is important because violence against women very often occurs in everyday life, whether in the family, school, community, work or with peers. Violence in general often happens to people who are defenseless, such as women. An educational institution which is actually a place for the growth and development of students in matters of literacy and also the development of soft skills should be a place or space that is safe and comfortable for them. However, it seems that this does not apply to survivors of cases of violence against women, especially in cases of sexual violence against women. Cases like this are real and happen a lot, both in schools and universities and have become an open secret that is deliberately forgotten by most of the parties involved, so the role of universities in providing protection against sexual violence against women in higher education environments is important.